Comparison of an antibody capture and a cell capture ligand-binding assay to quantify a monoclonal therapeutic in serum. (March 2011) - Spriggs, Franklin; Aggarwal, Poonam; Deng, Shibing; Soderstrom, Catherine; Donovan, Carol
Background: Ligand-binding assays are a tool used for the quantification of antibody therapies. When assay format changes are required during the drug development process it is advisable to assess these formats ensuring the resulting data can be compared. In this article, we outline the method and results obtained comparing an anti-idiotype capture and a cell-capture ligand-binding assay.Results: Comparison of results for all quality controls between assays were within acceptance limits, with the exception of the low quality control. Statistical analysis of the results demonstrated 95% power to detect a 20% difference between data sets. Subsequent analysis of unknown samples further confirmed 98% power to detect a 20% difference between data sets.Conclusion: Results obtained using two assay formats are statistically comparable to each other.